The Presence of Circulating Tumor Cell Cluster Characterizes an Aggressive Hepatocellular Carcinoma Subtype - Yu, Jing-Jing; Shu, Chang; Yang, Hui-Yuan; Huang, Zhao; Li, Ya-Ni; Tao, Ran; Chen, Yue-Yue; Chen, Qian; Chen, Xiao-Ping; Xiao, Wei (Frontiers in Oncology, 2021)
Background: Growing evidence suggests that circulating tumor cell (CTC) clusters may be an important factor in the metastatic process, but their role in hepatocellular carcinoma (HCC) remains unclear. This study aimed to characterize the molecular and clinical features of CTC cluster-positive human HCC, and to assess its prognostic value in HCC patients. Methods: The CTCs and CTC clusters were evaluated in 204 HCC patients using CellSearch™ System. The counts of CTCs and CTC clusters were correlated with different clinical features, while their associations with progression-free survival (PFS) and overall survival (OS) were evaluated integrally and hierarchically by Kaplan-Meier estimates or Cox proportional regression analysis. Five cases each of CTC cluster-negative and positive patients were selected for RNA sequencing analysis. The results of gene enrichment analysis were further verified using tissue microarray (TMA) by immunohistochemistry (IHC). Results: CTCs and CTC clusters were detected in 76(37.3%) and 19(9.3%) of 204 preoperative samples respectively. CTC cluster-positive HCC represented an aggressive HCC phenotype with larger tumor size, more frequent microvascular invasion, and higher tumor stages. The survival of HCC patients utilizing CTCs and CTC clusters individually showed prognostic significance, while joint analysis revealed patients in Group III (CTC ≥ 2 and CTC cluster > 0) had the worst outcome. Stratified analysis of outcomes in Barcelona Clinic Liver Cancer (BCLC) and TNM stages indicated that patients with CTC clusters had significantly poorer prognosis in each stage than those without CTC clusters. Moreover, the RNA sequencing and TMA staining results showed that CTC cluster-positive HCCs were usually associated with Wnt/β-catenin signaling activation. Conclusion: The presence of CTC clusters characterizes an aggressive HCC subtype. CTC clusters may be used as a biomarker in predicting the prognosis on each stage of malignancy in HCC, which provides evidence for formulating therapeutic strategies for more precise treatment.